Spreading the word groundings in the philosophy of language - Blackburn, Simon 1944- (Clarendon Pr., 1984)
This book provides a comprehensive introduction to many central aspects of the philosophy of language, among them representation, rule following, convention, intention and thought, realism, and particularly the substantial issues in the philosophy of truth and reference.